Colonization of lake Erie tributaries by Allocapnia recta (Capniidae) - Yasick, Alison L. (Illiesia, 2015)
Plecoptera display a variety of dispersal mechanisms. The most reduced of these, walking, is common for winter stoneflies in the family Capniidae. To examine dispersal in a winter stonefly, Allocapnia recta, we sequenced a fragment of the 16s rRNA mitochondrial gene from four adjacent Lake Erie drainages. Nineteen unique haplotypes were obtained from 107 specimens. The four watersheds explained 37% of the haplotype diversity and all pairwise contrasts among streams were statistically significant; not one haplotype was common to all four watersheds. This extreme level of divergence among populations separated briefly in both space and time suggest minimal if any measurable gene flow and therefore the possibility that geological processes may better explain northern colonization to the Great Lakes than may adult migration. One possibility is for post-glacial change in topography, in particular isostatic adjustment to raise land, which led to flow reversal at the headwaters of rivers along what now is Ohio%s Northern Divide, separating the Laurentian Great Lakes from the Ohio/Mississippi River system.
Keywords: entomology; stoneflies; Perlodidae; Plecoptera; Capniidae; distribution; migration; Allocapnia recta; population structure; haplotypes; mitochondrial DNA; mtDNA; Ohio; United States of America; USA